Como a Petrobras foi de vítima à ré? Lava Jato vs. vaza jato : instrumentalidade processual e limites penais da assistência direta - Silva, Thales Cassiano (2021)
The question that this thesis wants to see answered, emerges from the Petrobras criminal penalty in the United States, which has come to be, in the context of the CarWash operation in Curitiba. The outlook that has been employed to the research, is the one born from criminal sciences, locating the debate under the uses of international legal cooperation to sustain the transnational enforcement of the FCPA. Promoted from the fact that prosecuting agents from Carwash operation self-labeled themselves responsible for an effective legal cooperation in that jurisdiction, discussing that the fine applied to Petrobras was almost all repatriated to Brazil. Therefore, this work starts on prosecuting agent's official version and contrasts it with which has come public after the leaks obtained from The Intercept were released. In fact, that is the case study scope conceived in the third chapter. Before it, at specific chapters, there’s a positioning on the criminal-political interests and criminology arguments that justify the rise of mutual legal assistance after the cold war, as well as a debate on prescriptive and descriptive regents’ categories of international legal cooperation in criminal matters, especially to the ones referred to, as criminal procedures and international public law.